#tableforone: exploring representations of dining out alone on Instagram. Issue 5 (19th October 2020) - McKeown, Janet K. L.; Miller, Maggie C.
ABSTRACT: In contemporary western society connections with others have become more fluid. This fluidity, in turn, impacts how people think about, understand, and engage in leisure. For instance, more people are choosing to partake in leisure practices that have traditionally been done in the company of others, alone. Yet people who choose to engage in solo leisure may face stigmatization for doing so. With these ideas in mind, the purpose of this paper is to examine representations of dining out alone on Instagram associated with #tableforone. Our findings illustrate how people use #tableforone to represent the importance of valuing alone time and treating oneself. Our findings also demonstrate the ways #tableforone can be used to confront the stigma tied to engaging in public leisure practices alone.